2021
DOI: 10.1111/jop.13180
|View full text |Cite
|
Sign up to set email alerts
|

CDK4 and TERT amplification in head and neck mucosal melanoma

Abstract: Background Recent high‐throughput sequencing studies have revealed frequent CDK4 and TERT amplification in mucosal melanoma, suggesting that they are potential therapeutic targets. In this study, we investigated the statuses of CDK4 and TERT in head and neck mucosal melanoma (HNMM) with the aim of providing preclinical data to support future clinical trials. Methods In total, 29 HNMM samples were collected, including 16 oral mucosal melanoma (OMM) samples and 13 nasal cavity/sinuses melanoma (SNMM) samples. Fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Two recent whole-genome sequencing studies were able to associate amplifications in these regions with structural rearrangements [10,48]. Also in line with these reports, we observed that focal amplification of TERT at the 5p15 gene locus primarily occurred in tumors of the oral cavity [49]. Furthermore, we observed that 11q13-14 amplification was enriched in melanomas of the nasal cavity, which has not previously been reported.…”
Section: Discussionsupporting
confidence: 91%
“…Two recent whole-genome sequencing studies were able to associate amplifications in these regions with structural rearrangements [10,48]. Also in line with these reports, we observed that focal amplification of TERT at the 5p15 gene locus primarily occurred in tumors of the oral cavity [49]. Furthermore, we observed that 11q13-14 amplification was enriched in melanomas of the nasal cavity, which has not previously been reported.…”
Section: Discussionsupporting
confidence: 91%
“…The recent study conducted by Lyu et al revealed that amplification of CDK4 was often observed concurrently with TERT amplification in head and neck mucosal melanoma. Additionally, the study found that amplifications of CDK4 and TERT were correlated with higher levels of CDK4 and TERT protein expression [88]. These findings collectively suggest that gene amplification in the CDK4 pathway is a frequent genetic occurrence in the development of melanoma, and alterations in the copy number of genes within the CDK4 pathway could serve as a promising therapeutic target for mucosal melanoma.…”
Section: Aberrant Cdk4-prb Pathway Signaling Pathways In MMmentioning
confidence: 73%
“…The second consumer consideration relates to the fact that, in vivo , senescence escape and overexpression of TERT and CDK4 can be associated with various cancers 35,36 . There is to-date no evidence for DNA transfer from gene edited foods to humans 37 .…”
Section: Discussionmentioning
confidence: 99%